KONFLIK SOSIAL TOKOH DALAM NOVEL KAWI MATIN DI NEGERI ANJING KARYA ARAFAT NUR - Nurjannah; Radhiah; Ririn Rahayu (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the types of social conflicts experienced by the characters in the novel Kawi Matin di Negeri Anjing by Arafat Nur. This research employed a qualitative approach with a descriptive method. The data consisted of words, sentences, and paragraphs containing elements of social conflict. The source of the data was the novel Kawi Matin di Negeri Anjing by Arafat Nur. Data were collected using reading and note-taking techniques. The findings reveal 42 instances of social conflict, comprising: (1) 29 cases of personal conflict, (2) 8 cases of antisocial conflict, and (3) 5 cases of political conflict. These results indicate that the novel reflects the complexity of social interactions, both in personal and interpersonal domains, as well as in political contexts.